Amphiphilic hydrogel electrolyte and preparation method and application thereof
By preparing amphoteric hydrogel electrolytes, the challenges of self-repair and high thermoelectric potential in thermoelectric batteries were solved, realizing a wearable thermoelectric battery with high self-healing properties and high thermoelectric potential, suitable for self-powered wearable electronic devices.
Patent Information
- Application Number
- CN202310545974.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-05-15
AI Technical Summary
Existing thermoelectric batteries cannot simultaneously achieve self-repair and high thermoelectric potential, thus failing to meet the needs of self-powered wearable electronic devices.
An amphoteric hydrogel electrolyte was prepared by reacting a [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide solution with a crosslinking agent and an initiator in a polyethylene glycol solution to form a double-network amphoteric hydrogel, which was then immersed in an electrolyte solution containing potassium ferrocyanide and potassium ferrous cyanide to form an electrolyte with high self-healing properties and high thermoelectric potential.
It achieves a high self-healing rate of 78%, a stretchability of 300% after self-healing, and a thermoelectric potential of 3.5mV/K, making it suitable for wearable thermoelectric batteries and providing stable power output.
Smart Images

Figure CN116731261B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gel electrolyte materials and electrochemical energy storage technology, specifically to an amphoteric hydrogel electrolyte, its preparation method, and its application. Background Technology
[0002] Thermoelectric batteries, capable of converting heat into electrical energy with enormous thermoelectric potential, have attracted widespread attention in recent years. Existing research has demonstrated that the thermoelectric potential of these batteries is highly dependent on the structural entropy and concentration gradient of the redox couple in the electrolyte. Attracted by the inherent flexibility and stretchability of gel materials, researchers have recently applied these findings to gel-based thermoelectric batteries.
[0003] With the rapid development of electronic technology, gel batteries are evolving towards thinner, lighter, more flexible, and wearable designs to meet market demands for foldable and bendable electronic devices. In particular, the design of highly self-healing and stretchable thermoelectric batteries with high thermoelectric potential, such as electronic skin, has garnered increasing attention. On one hand, self-healing polymers based on physical cross-linking or external stimuli (such as heat and light) have been successfully developed and used for the mechanical recovery of devices. However, to achieve self-healing properties, these polymers are not suitable for using large amounts of solvents. On the other hand, widely accepted strategies to increase structural entropy and redox couple concentration differences to enhance thermoelectric potential rely on the use of large amounts of additives. Current research strategies struggle to simultaneously achieve self-healing and increased thermoelectric potential.
[0004] Therefore, there is still a lack of thermoelectric batteries that can simultaneously achieve intrinsic self-healing and high thermoelectric potential to meet the development needs of self-powered wearable electronic devices. Summary of the Invention
[0005] In view of this, one aspect of the present invention aims to provide an amphoteric hydrogel electrolyte that can alleviate the above-mentioned problems or at least alleviate them to some extent.
[0006] To achieve the above objectives, the technical solution adopted in this application is a method for preparing an amphoteric hydrogel electrolyte, comprising the following steps: 1) In an aqueous solution of polyethylene glycol, a [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide solution undergoes a polymerization reaction in the presence of a crosslinking agent and an initiator to obtain a double-network amphoteric hydrogel; 2) The double-network amphoteric hydrogel obtained in step 1) is immersed in an electrolyte solution containing potassium ferricyanide and potassium ferrocyanide to obtain the amphoteric hydrogel electrolyte.
[0007] In some embodiments, the crosslinking agent in step 1) is N,N-methylenebisacrylamide, and the initiator is potassium persulfate.
[0008] In some embodiments, the polymerization reaction in step 1) is carried out at 80°C for 12 hours.
[0009] In some embodiments, the mass ratio of polyethylene glycol to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide in step 1) is 1:100-3:100.
[0010] In some embodiments, the molar concentration ratio of potassium ferrocyanide to potassium ferrous cyanide is 1:1 to 1:1.5.
[0011] In some embodiments, the molar concentration of potassium ferrocyanide is 0.3 M, and the molar concentration of potassium ferrocyanide is 0.45 M.
[0012] In some embodiments, the electrolyte solution in step 2) further includes LiCl.
[0013] In some embodiments, the molar concentration of LiCl is 0.6M-3.6M.
[0014] In another aspect, the present invention provides an amphoteric hydrogel electrolyte prepared by the above-described method.
[0015] In another aspect, the present invention provides the application of the above-mentioned amphoteric hydrogel electrolyte in wearable thermoelectric batteries.
[0016] Compared with existing technologies, the amphoteric hydrogel electrolyte of this application embodiment has an effective cleavage-activated reversible crosslinking effect and expands the structural entropy difference of the redox couple, exhibiting high self-healing properties of 78%, a stretchability of up to 300% after self-healing, and a thermoelectric potential of 3.5 mV / K. It can be applied to thermoelectric batteries, providing a promising prospect for the development of thermoelectric batteries for self-powered wearable electronic devices. Attached Figure Description
[0017] Figure 1 This is a schematic diagram illustrating the preparation principle of the amphoteric hydrogel electrolyte according to an embodiment of the present invention.
[0018] Figure 2 This is a schematic diagram of the amphoteric hydrogel electrolyte before and after polymerization according to an embodiment of the present invention.
[0019] Figure 3 The image shows the FTIR spectrum of the PP1 hydrogel in Example 1 of this invention.
[0020] Figure 4 This is a SEM image of the PP1 hydrogel from Embodiment 1 of the present invention.
[0021] Figure 5 This is a SEM image of the amphoteric hydrogel electrolyte of Embodiment 1 of the present invention.
[0022] Figure 6 This is a comparison of stress-strain curves before and after self-healing of a dual-network amphoteric hydrogel with different PEG contents in an embodiment of the present invention and a PPO hydrogel in Comparative Example 1.
[0023] Figure 7 This is a comparison chart of the self-healing rates of the dual-network amphoteric hydrogels with different PEG contents in this embodiment of the invention and the PPO hydrogel in Comparative Example 1.
[0024] Figure 8 The thermoelectric potential of PP1 hydrogel soaked in electrolyte solutions containing different concentrations of K3Fe(CN)6 and K4Fe(CN)6 in an embodiment of the present invention.
[0025] Figure 9 The graph shows the temperature difference versus thermoelectric voltage relationship between PP1 hydrogel and the amphoteric hydrogel electrolyte of Example 2 of this invention.
[0026] Figure 10 The UV-Vis spectrum is shown for a mixed solution containing K3Fe(CN)6 and K4Fe(CN)6 without the addition of SBMA.
[0027] Figure 11 The UV-Vis spectrum of the mixture containing K3Fe(CN)6 and K4Fe(CN)6 with added SBMA.
[0028] Figure 12 The thermoelectric potential of PP1 hydrogel soaked in electrolyte solutions containing 0.45M K4Fe(CN)6, 0.3M K3Fe(CN)6 and different concentrations of LiCl is shown in this embodiment of the invention.
[0029] Figure 13 The Nyquist plots show the PP1 hydrogel and the amphoteric hydrogel electrolytes of Examples 1 and 2 of this invention.
[0030] Figure 14 The graph shows a comparison of the thermoelectric battery performance of PP1 hydrogel and the amphoteric hydrogel electrolytes of Examples 1 and 2 of this invention.
[0031] Figure 15 The stress-strain curves of the amphoteric hydrogel electrolytes in Embodiment 1, Embodiment 2, and Comparative Example 2 of the present invention before and after self-healing are shown.
[0032] Figure 16 The self-healing rate of the amphoteric hydrogel electrolytes in Embodiment 1, Embodiment 2, and Comparative Example 2 of the present invention is shown.
[0033] Figure 17 The thermoelectric potential of the amphoteric hydrogel electrolyte after repeated self-healing in Embodiment 1 of the present invention.
[0034] Figure 18 The thermoelectric potential of the amphoteric hydrogel electrolyte after self-healing and stretching in Embodiment 1 of the present invention is shown.
[0035] Figure 19 The thermoelectric potential of the amphoteric hydrogel electrolyte in Embodiment 1 of the present invention at low temperature.
[0036] Figure 20 This is a comparison of the thermoelectric potential, ionic conductivity, power factor, stretchability, and self-healing properties of the thermoelectric battery of Embodiment 1 of the present invention with those of previously reported batteries.
[0037] Figure 21 This is a schematic diagram of a thermoelectric battery illuminating an LED light with the help of a voltage amplifier, according to an embodiment of the present invention.
[0038] Figure 22 for Figure 19 The thermal voltage output of the thermoelectric battery under various extreme conditions.
[0039] Figure 23 This diagram illustrates a wearable TEC (Technical Equipment) of Embodiment 1 that collects body heat into electrical energy.
[0040] Terminology Explanation
[0041] Unless otherwise stated, the following terms and phrases as used herein have the following meanings:
[0042] wt%: percentage by mass.
[0043] KPS: Potassium persulfate.
[0044] BIS: N,N'-methylenebisacrylamide.
[0045] SBMA: [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide.
[0046] PEG: Polyethylene glycol.
[0047] M: Volumetric molar concentration.
[0048] S i Thermoelectric potential.
[0049] σ i : Ionic conductivity.
[0050] PF: Power Factor.
[0051] TECs: Abbreviation for thermocells.
[0052] Nyquist plot: polar coordinate plot. Detailed Implementation
[0053] To make the objectives and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application.
[0054] Chemicals and materials
[0055] All materials were purchased and used without further processing.
[0056] [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA) and potassium ferrocyanide (K3Fe(CN)6) were purchased from Beijing InnoChem Chemical Technology Co., Ltd. N',N-methylenediacrylamide (BIS), potassium persulfate (KPS), polyethylene glycol (PEG, Mw = 20000), and anhydrous lithium chloride (LiCl) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Potassium ferrocyanide (K4Fe(CN)6) was from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0057] Electrochemical characterization
[0058] Chemical structure and composition were analyzed by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR, Nicolet 760). The microstructure was characterized using scanning electron microscopy (SEM, Hitachi S-4800, Japan). UV-Vis absorption characteristics were recorded on a Lamda 35 spectrophotometer. Freeze-thaw resistance was analyzed by differential scanning calorimetry (DSC, TAQ2000). Mechanical properties and self-healing properties were analyzed by recording stress-strain curves of the samples (using a fully computerized tensile peel tester, Guangdong Zhongye Precision Scientific Instruments Co., Ltd.), where the self-healing rate was calculated as the ratio of the fracture strength before and after self-healing.
[0059] Measurement and calculation of ionic conductivity
[0060] The ionic conductivity (σ) of the sample i The ions were obtained from electrochemical impedance spectroscopy (EIS) using an electrochemical workstation (CHI660E). In the EIS test, the sample was sandwiched between two stainless steel plates. The ionic resistance was obtained by extrapolating the curve using an equivalent abscissa. σ was then calculated according to formula (1). i .
[0061]
[0062] Where l and A are the sample thickness and cross-sectional area, and R is the ion resistance.
[0063] Thermoelectric potential measurement and calculation
[0064] Thermoelectric potential of the sample (S) i The temperature difference was measured using a self-made temperature gradient platform. Cold water (cold end) and a ceramic heater (hot end) were used to set the temperature difference, and the ceramic heater was powered by a DC power supply. Here, the temperature difference (ΔT) between the cold and hot ends of the sample was detected by attaching two thermocouples to the cold and hot ends. At ΔT, the corresponding open-circuit voltage (i.e., thermal voltage, ΔU) of the sample was measured by a Keithley 6510 with two gold wires as electrodes. Based on the obtained ΔU and ΔT, S was calculated according to formula (2). i .
[0065] S i =-ΔU / ΔT (2)
[0066] To prevent moisture loss during long-term measurements, the samples were sealed with plastic wrap (Shanghai Liangjie Environmental Protection Technology Co., Ltd.). Furthermore, the σ value at sub-zero temperatures was measured by placing the samples and testing platform in a high and low temperature testing chamber. i and S i .
[0067] Example 1
[0068] 1) Preparation of dual-network amphoteric hydrogels
[0069] In an aqueous solution of PEG, SBMA is polymerized in the presence of KPS initiator and BIS crosslinking agent to prepare a dual-network amphoteric hydrogel (P(SBMA) / PEG hydrogel) via chemical oxidative polymerization. The first network structure is composed of PEG, and the second network structure is formed by the polymerization of SBMA. The polymerization of P(SBMA) is initiated by KPS and crosslinked by BIS to form a three-dimensional structure. During the polymerization process, the first and second network structures interpenetrate to form the dual-network hydrogel. The reaction principle is as follows: Figure 1 As shown.
[0070] The specific steps are as follows: Dissolve 28.0g of SBMA in 25.0ml of deionized water and stir magnetically to obtain a 4.0M SBMA solution. Then, add 4.9g of pre-prepared PEG aqueous solution (0.057g / g, i.e., 0.057g of PEG dissolved in 1g of PEG aqueous solution) to the above solution and stir magnetically. Subsequently, add 56.0mg of BIS and 112mg of KPS while stirring thoroughly. Finally, degas the resulting solution and inject it into a silicon mold. A physical sample can be referenced. Figure 2The image on the left shows the solution polymerized at 80°C for 12 hours, yielding the double-network amphoteric hydrogel of Example 1. A physical sample can be referenced. Figure 2 The image on the right. Figure 2 Step 1) describes the successful preparation of a dual-network amphoteric hydrogel via chemical polymerization. In this Example 1, the mass ratio of PEG to SBMA in the reaction was 1:100, and the prepared dual-network amphoteric hydrogel is designated as PP1.
[0071] In other alternative embodiments, the amount of PEG aqueous solution added in step 1) can be 9.8 g and 14.7 g, thereby obtaining amphoteric hydrogels with different PEG contents, denoted as PP2 and PP3, respectively. It is understood that the amount of PEG aqueous solution added can also be other values.
[0072] 2) Preparation of amphoteric hydrogel electrolytes
[0073] The double-network amphoteric hydrogel prepared in step 1) was immersed in an electrolyte solution containing 1.8 M LiCl, 0.45 M K4Fe(CN)6, and 0.3 M K3Fe(CN)6 for 0.5 h to obtain the amphoteric hydrogel electrolyte of Example 1, denoted as LiCl·Fe(CN)6. 4- / 3- ·PP1.
[0074] In other alternative embodiments, the electrolyte in step 2) may contain 0.2M K4Fe(CN)6 and 0.2M K3Fe(CN)6, or may contain 0.3M K4Fe(CN)6 and 0.3M K3Fe(CN)6, or may contain 0.15M K4Fe(CN)6 and 0.1M K3Fe(CN)6, or may contain 0.3M K4Fe(CN)6 and 0.2M K3Fe(CN)6;
[0075] The electrolyte solution may contain 0.6 M LiCl and 0.45 M K₄Fe(CN)₆ and 0.3 M K₃Fe(CN)₆, or 1.2 M LiCl, 0.45 M K₄Fe(CN)₆ and 0.3 M K₃Fe(CN)₆, or 2.4 M LiCl, 0.45 M K₄Fe(CN)₆ and 0.3 M K₃Fe(CN)₆, or 3.0 M LiCl, 0.45 M K₄Fe(CN)₆ and 0.3 M K₃Fe(CN)₆, or 3.6 M LiCl, 0.45 M K₄Fe(CN)₆ and 0.3 M K₃Fe(CN)₆. It is understood that K₄Fe(CN)₆, K₃Fe(CN)₆ and LiCl may also be in other concentrations.
[0076] 3) Preparation of TECs
[0077] The amphoteric hydrogel electrolyte from step 2) of Example 1 was fabricated to a size of 7×7×5cm. 3 The size of the thermoelectric arms is used as the electrodes. One hundred thermoelectric arms are clamped together in series using copper foil as electrodes. Then, the series-connected thermoelectric arms are attached to a polyethylene terephthalate substrate to fabricate a hydrogel battery. Because the amphoteric hydrogel electrolyte is flexible and wearable, this battery can be worn on the arm and utilizes body heat to form wearable TECs, such as... Figure 23 As shown.
[0078] Example 2
[0079] The difference between Example 2 and Example 1 is that in step 2), the double-network amphoteric hydrogel prepared in step 1) is immersed in an electrolyte solution containing 0.45M K4Fe(CN)6 and 0.3M K3Fe(CN)6 to obtain the hydrogel electrolyte of Example 2 (denoted as Fe(CN)6). 4- / 3- ·PP1). Apart from that, the other steps are the same.
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that the amount of PEG aqueous solution added in step 1) is 0, that is, no PEG aqueous solution is added, and the P(SBMA) amphoteric hydrogel of Comparative Example 1 is prepared, denoted as PPO. Other than that, the other steps are the same.
[0082] Comparative Example 2
[0083] The difference between Comparative Example 2 and Example 1 is that in step 2), the double-network amphoteric hydrogel prepared in step 1) is immersed in an electrolyte solution containing 1.8M LiCl to obtain the amphoteric hydrogel electrolyte of Comparative Example 2, denoted as LiCl·PP1. Other than this, the steps are the same.
[0084] Results and Discussion
[0085] The chemical structure of the dual-network amphoteric hydrogel (PP1) of Example 1 was analyzed by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and the results are as follows: Figure 3 At 1036cm -1 and 1174cm -1 The two distinct characteristic peaks are due to -SO 3- Produced by the symmetric and asymmetric stretching vibrations of the functional group, and at 1479 cm⁻¹ -1 and 1721cm -1 The peaks are respectively composed of -N + (CH3)2 and ester groups are generated. This indicates that step 1) successfully prepared an amphoteric hydrogel. Furthermore, the microstructure of the PP1 hydrogel from Example 1 before and after immersion in the electrolyte solution was studied using SEM, and the results are as follows... Figure 4 and Figure 5 As shown, the former and the latter exhibit a dense morphology and numerous pores, respectively. This significant difference is caused by the adsorption of water and electrolytes, leading to a large difference in ionic conductivity.
[0086] Mechanical and self-healing properties
[0087] Figure 6 (Solid line) shows the stress-strain curves of amphoteric hydrogels with different PEG contents. It can be seen that P(SBMA) in Comparative Example 1 exhibits the highest tensile strength (46 kPa) and elongation at break of 230%. With increasing PEG content, the tensile strength of the prepared double-network amphoteric hydrogel decreases to 17 kPa, while the elongation at break reaches its highest value of 434% with PP3 (the mass ratio of PEG to SBMA in the preparation of this double-network amphoteric hydrogel is 3:100). To investigate its self-healing properties, stress-strain tests were performed on amphoteric hydrogels with different PEG contents after self-healing, as shown in the figure. Figure 6 As shown by the dashed line, the self-healing rates of the P(SBMA) hydrogel in Comparative Example 1 and the dual-network amphoteric hydrogel PP1 in Example 1, based on the ratio of fracture strength after healing to that before healing, were 92% and 90%, respectively. Figure 7 The dual-network amphoteric hydrogel of this embodiment exhibits excellent self-healing properties. This excellent self-healing property originates from the anionic (-SO3) - ) and cations (-N) + The presence of (CH3)2CH2) results in strong electrostatic interactions between zwitterionic P(SBMA) chains. Once the network structure breaks under external force, it can recover under reversible electrostatic interactions when the structural fragments come back together, thus achieving self-healing.
[0088] Thermoelectric battery performance
[0089] The thermal voltage of a thermoelectric battery originates from the thermogalvanic effect of the redox couple in the electrolyte; that is, if two electrodes in contact with the electrolyte gel have different temperatures, a potential difference will be generated between them. In this application, an amphoteric hydrogel electrolyte and electrodes with a temperature difference form a thermoelectric battery, wherein Fe(CN)6... 4- It is oxidized to Fe(CN)6 on the hot side. 3- Fe(CN)6 3- It is reduced to Fe(CN)6 on the cold side. 4- That is, the redox couple is Fe(CN)6 4- / 3- This generates electrical energy. Figure 8 The thermoelectric potentials of PP1 hydrogels immersed in electrolyte solutions containing different concentrations of K3Fe(CN)6 and K4Fe(CN)6 are shown. In the figure, Fe...4- and Fe 3- These are abbreviations for K4Fe(CN)6 and K3Fe(CN)6, respectively. It can be seen that the amphoteric hydrogel electrolyte of Example 2 (the PP1 hydrogel was soaked in an electrolyte solution containing 0.45M K4Fe(CN)6 and 0.3M K3Fe(CN)6) achieved a maximum thermoelectric potential of 2.04 mV / K. Figure 9 The graph shows the temperature difference versus thermoelectric voltage relationship between the bare PP1 hydrogel and the amphoteric hydrogel electrolyte of Example 2 of this invention. The bare PP1 hydrogel is the PP1 hydrogel that was not impregnated with the electrolyte solution in step 1). It can be seen that the thermoelectric potential of the amphoteric hydrogel electrolyte of Example 2 is significantly higher than that of the previously reported water-based Fe(CN)6. 4- / 3- Thermoelectric cell (1.4mV / K) [1-2] And bare PP1 hydrogel (0.44 mV / K). This significantly enhanced thermoelectric potential indicates that the total thermoelectric potential does not solely originate from Fe(CN)6. 4- / 3- Electrical pair or bare PP1.
[0090] To investigate the effect of SBMA on Fe(CN)6 4- / 3- The effect of redox couples was investigated by measuring the UV-Vis absorption spectra of K3Fe(CN)6 and K4Fe(CN)6 solutions with and without SBMA. The results are shown in [Figure number missing]. Figures 10 to 11 Clearly, the addition of SBMA has an effect on Fe(CN)6. 3- There was no effect, but after adding SBMA, Fe(CN)6 4- A significant blue shift was observed. This is because it has a special structure, where -N + (CH3)2 partially exhibits a cation-dissociation behavior (chaotropic cation). It can selectively react with Fe(CN)6, which has a higher charge density. 4- This process occurs, leading to its complex hydration structure and thus expanding the Fe(CN)6... 4- / 3- The structural entropy difference of the redox couple results in a higher thermoelectric potential. Therefore, amphoteric SBMA plays a crucial "two birds with one stone" role, not only endowing the hydrogel with excellent self-healing capabilities but also, through its interaction with Fe(CN)6... 4- The effect selectively increases the thermoelectric potential.
[0091] To further improve the performance of the amphoteric hydrogel electrolyte, different concentrations of LiCl solution were added to electrolyte solutions containing 0.3M K3Fe(CN)6 and 0.45M K4Fe(CN)6 to incorporate the ionic thermoelectric (i-TE) effect. Figure 12It can be seen that when the LiCl concentration increases to 1.8 M, the thermoelectric potential of the amphoteric hydrogel electrolyte increases from 2.04 mV / K to 3.50 mV / K, but the effect of further increasing the LiCl concentration on the thermoelectric potential becomes smaller.
[0092] In addition to thermoelectric potential, the ionic conductivity (σ) of these amphoteric hydrogel electrolytes was determined by electrochemical impedance spectroscopy (EIS). i Studies have also been conducted, such as Figure 13 The Nyquist plots show the bare PP1 hydrogel and the amphoteric hydrogel electrolytes of Examples 1 and 2 of this invention. These results were obtained from electrochemical impedance spectroscopy (EIS) and are used to analyze the resistance of the tested electrochemical systems. Figure 14 The graph shows a comparison of the thermoelectric cell performance of bare PP1 hydrogel and the amphoteric hydrogel electrolytes of Examples 1 and 2 of this invention to evaluate the power factor (PF). It can be seen that, compared with bare PP1 hydrogel, the PP1 hydrogel soaked in an electrolyte solution containing K4Fe(CN)6 and K3Fe(CN)6 or soaked in an electrolyte solution containing K4Fe(CN)6, K3Fe(CN)6 and LiCl shows a significant decrease in resistance, from 0.09 S / m. -1 Significantly enhanced to 17.1 S m -1 and 22.1S m -1 This enhanced σ i The absorption of the electrolyte solvent, water, promotes mass transfer and increases ion concentration. This is due to the aforementioned potential thermoelectric potential and σ... i The PF value of the amphoteric hydrogel electrolyte ranges from 0.02 μW / m. -1 K -2 Significantly increased to 72 μW m -1 K -2 Ultimately reaching 270 μW m -1 K -2 .
[0093] Adaptability assessment of thermoelectric batteries
[0094] Self-healing and stretchability are crucial for wearable electronic devices. PP1 hydrogel was immersed in different electrolyte solutions for stretching and self-healing tests to evaluate the impact of different electrolyte solutions on its adaptability. Since swelling in the hydrogel electrolyte sacrifices some stretchability and self-healing properties, the PP1 hydrogel was first impregnated with the electrolyte solution and then evaporated with water at room temperature for 1 hour to obtain the same dimensions as before swelling. The stress-strain curves of the amphoteric hydrogel electrolytes of Examples 1, 2, and Comparative Example 2 before and after self-healing are shown below. Figure 15 As shown. The amphoteric hydrogel electrolyte of Example 1 can be stretched to 388% and can still be stretched to 300% after self-healing. The amphoteric hydrogel electrolyte of Example 2 also performed well. Figure 16 The chart shows a comparison of the self-healing rates of the amphoteric hydrogel electrolytes of Embodiment 1, Embodiment 2, and Comparative Example 2 of the present invention. It can be seen that the amphoteric hydrogel electrolyte of Embodiment 1 can maintain a self-healing rate of 78%, and the amphoteric hydrogel electrolyte of Embodiment 2 is not much different from that of Embodiment 1.
[0095] The thermoelectric potential of the amphoteric hydrogel electrolyte of Example 1 was then tested under various extreme conditions to evaluate its applicability. Figure 17 The results show that after six cycles of fracture / self-healing, the thermoelectric potential of the amphoteric hydrogel electrolyte in Example 1 decreased slightly from an initial 3.5 mV / K to 2.79 mV / K. Furthermore, its thermoelectric potential remained very stable under various tensile strains after self-healing. Figure 18 Furthermore, its thermoelectric potential is also very stable at low temperatures. Figure 19 ).
[0096] Finally, the aforementioned self-made temperature gradient platform was connected to the amphoteric hydrogel electrolyte of Example 1 to form a thermoelectric battery, and its battery performance was tested. Figure 20 This shows a comprehensive comparison of the performance of this thermoelectric cell with other previously reported cells. [3-9] On the one hand, benefiting from the amphoteric SBMA and flexible PEG polymer, the amphoteric hydrogel electrolyte exhibits high self-healing properties (90%) and stretchability (371%). Furthermore, due to the presence of LiCl, the amphoteric hydrogel electrolyte achieves further self-healing at -10°C. On the other hand, due to the interaction of the dual-network amphoteric hydrogel and electrolyte, it possesses a large thermoelectric potential (3.5 mV / K) and high σ... i (22.1S m -1 ) and PF (270μW m -1 K -2 This achieves excellent thermoelectric battery performance.
[0097] Applications of wearable hydrogel thermoelectric batteries
[0098] like Figure 21 As shown, an amphoteric hydrogel electrolyte from Example 1 was used as a thermoelectric battery generator. A simple thermoelectric battery was formed using the heat from a finger as a heat source to evaluate its potential in self-powered wearable electronic devices. This thermoelectric battery lit an LED light with the aid of a voltage amplifier. The results demonstrate the potential of the amphoteric hydrogel electrolyte in thermoelectric conversion. To evaluate wearability, the thermoelectric battery was bent and stretched. After self-healing, and even in the stretched state after self-healing, the LED light remained lit. Furthermore, changes in thermal voltage were monitored under multiple bends (90°), stretches (50%), self-healing, and stretches after self-healing. The results are as follows: Figure 22As shown, the thermal voltage of the thermoelectric cell changes very little during multiple bending and stretching processes, and it can recover quickly and completely after self-healing, remaining constant during stretching after self-healing.
[0099] Finally, to harvest body heat into electrical energy without a voltage amplifier, as described in step 3 above, using the amphoteric hydrogel electrolyte of Example 1 as thermoelectric arms, 100 thermoelectric arms were assembled into an array and worn on the arm to form wearable TECs. (See...) Figure 23 The wearable TECs achieved a high thermal voltage of 0.77V under a small temperature difference of 3K.
[0100] This application describes the successful preparation of an amphoteric hydrogel electrolyte by interpenetrating an amphoteric polymer (P(SBMA)) into a polyethylene glycol (PEG) network via oxidative polymerization to form a double-network amphoteric hydrogel, which is then immersed in an electrolyte solution. When applied to a thermoelectric battery, it exhibits excellent self-healing properties, post-healing stretchability, and high thermoelectric potential. Specifically, due to the strong electrostatic interaction between the anions and cations in the amphoteric P(SBMA), the prepared amphoteric hydrogel electrolyte achieves a 78% self-healing rate and 00% post-healing stretchability. Furthermore, the thermoelectric potential is significantly increased to 2.04 mV / K due to the increased structural entropy difference of the redox couple caused by the amphoteric polymer. The prepared thermoelectric battery can stably power an LED light under extreme conditions (bending, stretching, self-healing, and post-healing stretching), using the heat from a finger as a heat source, and can provide a stable thermal voltage under these extreme conditions, achieving effective body heat harvesting. This has significant implications for the development of thermoelectric batteries and wearable electronic devices.
[0101] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0102] Previous reports on related literature
[0103] [1]Duan JJ, Feng G, Yu BY, Li J, Chen M, Yang PH, et al. Aqueousthermogalvanic cells with a high Seebeck coefficient for low-grade heatharvest. Nat. Commun. 2018; 9:5146.
[0104] [2]Kim T,Lee J S,Lee G,Yoon H,Yoon J,Kang T J,et al.High thermopowerof ferri / ferrocyanide redox couple in organic-water solutions.NanoEnergy.2017;31:160-167.
[0105] [3]Lei Z Y,Gao W,Wu P Y.Double-network thermocells with extraordinarytoughness and boosted power density for continuous heatharvesting.Joule.2021;5(8):2211-2222.
[0106] [4]Zhang D,Mao Y,Ye F,Li Q,Bai P J,He W,et al.Stretchablethermogalvanic hydrogel thermocell with record-high specific output powerdensity enabled by ion-induced crystallization.Energ.Environ.Sci.2022;15(7):2974-2982.
[0107] [5]Gao W,Lei Z Y,Zhang C B,Liu X D,Chen Y P.Stretchable and freeze-tolerant organohydrogel thermocells with enhanced thermoelectric performancecontinually working at subzero temperatures.Adv.Funct.Mater.2021;31(43):2104071.
[0108] [6]Peng P,Zhou J Q,Liang L R,Huang X,Lv H C,Liu Z X,et al.Regulatingthermogalvanic effect and mechanical robustness via redox ions for flexiblequasi-solid-state thermocells.Nano Micro Lett.2022;14(1):81.
[0109] [7]Liang L R,Lv H C,Shi X L,Liu Z X,Chen G M,Chen Z G,et al.Aflexiblequasi-solid-state thermoelectrochemical cell with high stretchabilityas an energy-autonomousstrain sensor.Mater.Horiz.2021;8(10):2750-2760.
[0110] [8]Pu S R,Liao Y T,Chen K L,Fu J,Zhang S L,Ge L R,etal.Thermogalvanic hydrogelfor synchronous evaporative cooling and low-gradeheat energy harvesting.Nano Lett.2020;20(5):3791-3797.
[0111] [9]Gao W,Lei Z Y,Chen W W,Chen Y P.Hierarchically anisotropicnetworks todecouple mechanical and ionic properties for high-performancequasi-solid thermocells.ACSNano.2022;16(5):8347-8357.
Claims
1. A method for preparing an amphoteric hydrogel electrolyte, characterized in that, Including the following steps: 1) In an aqueous solution of polyethylene glycol, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is polymerized in the presence of a crosslinking agent and an initiator to obtain a double-network amphoteric hydrogel; 2) Immerse the double-network amphoteric hydrogel obtained in step 1) in an electrolyte solution containing potassium ferrocyanide, potassium ferrocyanide and LiCl to obtain the amphoteric hydrogel electrolyte, wherein the molar concentration of LiCl is 0.6M-3.6M. In step 1), the mass ratio of polyethylene glycol to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 1:100-3:
100.
2. The preparation method according to claim 1, characterized in that, The crosslinking agent in step 1) is N,N-methylenebisacrylamide, and the initiator is potassium persulfate.
3. The preparation method according to claim 1, characterized in that, The polymerization reaction in step 1) was carried out at 80°C. o Polymerize at C for 12 hours.
4. The preparation method according to claim 1, characterized in that, The molar ratio of potassium ferrocyanide to potassium ferrous cyanide is 1:1 to 1:1.
5.
5. The preparation method according to claim 1, characterized in that, The molar concentration of potassium ferrocyanide is 0.3 M, and the molar concentration of potassium ferricyanide is 0.45 M.
6. An amphoteric hydrogel electrolyte, characterized in that... Prepared by the method of any one of claims 1-5.
7. The application of the amphoteric hydrogel electrolyte as described in claim 6, characterized in that... Thermoelectric batteries for wearable devices.
Citation Information
Patent Citations
Zwitterionic hydrogel, electrolyte, secondary battery or supercapacitor, and electric device
CN113698718A
Preparation method and application of high-performance thermoelectric hydrogel based on ion conduction
CN113881068A
